Comparing the precision of two digital PCR applications for copy number comparisons in protists - Megan Gross; Thorsten Stoeck; Quentin Mauvisseau; Audun Schrøder-Nielsen; Micah Dunthorn (Scientific Reports)
Abstract Microorganisms play key roles in ecosystem functioning, making reliable methods for assessing their dynamics essential. Advances in molecular technologies now enable their quantification in environmental samples based on DNA marker genes. Among these, digital PCR has emerged as a powerful tool for detecting and quantifying organisms based on their gene copies, with numerous platforms that are currently available. However, these platforms differ in their underlying technologies, and comparative studies that evaluate the performance and reproducibility remain limited. Here we compared different platform parameters across the QX200 digital droplet PCR from Bio-Rad and the QIAcuity One nanoplate-based digital PCR from QIAGEN. We used synthetic oligonucleotides and DNA extracted from varying cell numbers of the ciliate Paramecium tetraurelia and additionally tested the impact of two restriction enzymes on gene copy number quantification. Both platforms demonstrated similar detection and quantification limits and yielded high precision across most analyses. We found a general tendency of higher precision using the HaeIII restriction enzyme instead of EcoRI, especially for the QX200 system. Gene copy number estimates from ciliate DNA were reproducible between platforms and showed a linear trend for an increasing number of cells for both platforms. These findings highlight the importance of cross-platform evaluations to ensure robust and reproducible gene copy number analysis in unicellular eukaryotes and support a potential broader application of digital PCR in environmental monitoring studies.